Nature-Based Land Management Practices and Yield Dynamics in Oil Palm Production: Insights From Indonesian Smallholder Growers - Kibrom T. Sibhatu; Martin Paul Jr. Tabe-Ojong; Hermanto Siregar (Agricultural Economics, 2025)
Nature-based land management (NLM) practices are increasingly promoted for their potential to bridge yield gaps and increase overall crop production. Yet, the extent of NLM adoption, the factors driving it, and its impact on yields remain unknown, particularly among smallholder farmers. This study addresses this knowledge gap using a unique three-round panel dataset from independent smallholder oil palm growers in Indonesia, focusing on three main NLM practices: composting, manual weeding, and organic soil amendments (SA) using lime and gypsum. We employ panel data estimators and a multivariate probit model to examine the yield effects of these practices and assess any potential interdependencies among them. Our findings indicate that the adoption of NLM practices among smallholder growers have been low and inconsistent. We identify several socioeconomic, agricultural, and biophysical factors that contribute to these low and inconsistent adoption rates. Our analysis further reveals little interdependence among the NLM practices, with none displaying a statistically significant positive association with oil palm yields. However, the application of fertilizers and herbicides is associated with higher yields. When we do not control for these yield-increasing inputs, only SA using lime and gypsum shows a positive association with yield gains. Our findings illustrate the complex relationship between NLM practices and oil palm yields among smallholders, shedding light on their~potential limitations and challenges.
Keywords: 330; nature-based land management; oil palm; smallholder farmers; sustainable intensification; tropical rainforests